Controllable N Doped in Carbon Nanolayers@Mo2C Nanodots as Electrocatalyst Boosts High‐Efficient Hydrogen Production. (3rd November 2022) - Mao, Ziyao; Wang, Yating; Liu, Rui; Sun, Jingjing; Liu, Bichan; Zhao, Ruihua; Du, Jianping
Abstract: Mo2 C is one of the promising alternatives to the precious metal catalyst for hydrogen evolution reaction (HER). However, it is still challenging to prepare highly dispersed Mo2 C and prevent nanoparticles (NPs) from sintering during high‐temperature carbonization. Herein, a strategy is proposed to realize dual purposes that confine the coalescence of Mo2 C NPs and redistribute charge density by regulating N‐doped contents. As‐synthesized molybdenum carbide nanodots are well dispersed on the N‐doped carbon nanolayers, and the size of Mo2 C is uniform and less than 5 nm. The HER tests reveal that as‐prepared Mo2 C nanodots exhibit excellent electrocatalytic activity for HER and long‐term stability. Theory calculation proves that optimizing N doping amount can tune hydrogen adsorption free energies and redistribute charge density. The present study provides insight into the impact of nitrogen doped in C/Mo2 C and also a synthetic route to achieve heteroatom doping and size control for the synthesis of nanocatalysts beyond Mo2 C. Abstract : Confining coalescence of Mo2 C nanoparticles and redistributing charge density are achieved by regulating N‐doped contents. As‐synthesized molybdenum carbide nanodots are well dispersed on the N‐doped carbon nanolayers, and H adsorption free energy is controlled, which exhibits excellent electrocatalytic activity for hydrogen evolution reaction and long‐term stability.